Alteração da qualidade do solo em zona ripária sob diferentes usos: potencial de poluição para um manancial tropical - Faria, Bruno Gazola de (2013)
The demographic growth press environments that are more susceptible to perturbations, like riparian areas, without knowing about the effects of replacing these natural environments by different land uses on soil quality and, consequently, on watershed. The study of soil quality has evolved as an important tool for soil sustainable management of this component of the biosphere that affects aquatic and terrestrial ecosystems functions. Thus, physical and chemical soil proprieties were measured to assess soil quality under different land uses (agricultural, pasture, urban, industrial and natural vegetation,) in the riparian zone of Extremoz Lake, an important human water source, evaluating whether the soil offers potential risk to water pollution. Data were subjected to descriptive statistics and Principal Component Analysis (PCA). The results showed negative changes in soil quality such as alkalinization and increase in P, Pb, Mn and Zn contents in most anthropized areas. The sandy texture and low organic matter content in all soils showed the fragility of the soil to erosion and leaching of elements in excess to water bodies, evidencing that this soils has potential to diffuse contaminants. Conservative management of soil is necessary to provide an adequate ecological state in riparian zones of the Extremoz Lake, thus allowing controlling and buffering diffuse sources of pollution to this important water supply source